How microplastics affect chiral illicit drug methamphetamine in aquatic food chain? From green alga (Chlorella pyrenoidosa) to freshwater snail (Cipangopaludian cathayensis). (March 2020) - Qu, Han; Ma, Ruixue; Barrett, Holly; Wang, Bin; Han, Jiajun; Wang, Fang; Chen, Pin; Wang, Wei; Peng, Guilong; Yu, Gang
Graphical abstract: Highlights: Methamphetamine could be adsorbed by microplastics in water. The toxicity of methamphetamine was aggravated significantly by microplastics. Microplastics increase the filter-feeding fate of snail. Microplastics increase the enrichment of R-methamphetamine in aquatic organism. Showing the bio-effect of microplastics and methamphetamine through aquatic food chain. Abstract: The biological impacts of microplastics on many organisms have been well documented. However, the combined effects of microplastics and chiral chemicals on the aquatic food chain are less clear. In the present study, the enantioselective environmental behaviors of methamphetamine co-exposed with microplastics through an aquatic food chain (from Chlorella pyrenoidosa to Cipangopaludian cathayensis ) have been investigated in a laboratory environment. It was found that the acute toxicity of methamphetamine against these two species was significantly increased in the presence of microplastics: Chlorella pyrenoidosa showed an EC50 shift from 0.77 to 0.32 mg L −1, while cipangopaludian cathayensis showed an LC50 shift from 4.15 to 1.48 mg L −1, upon the addition of microplastics as a co-contaminant with methamphetamine. Upon exposure to methamphetamine and microplastics, the oxidative damage of algae (19.9 to 36.8 nmol mgprot −1 ), apoptosis (increase about 2.17 times) and filtration rate (41.2 to 65.4 mL h −1 ) of snails were observably higher when compared to exposure to methamphetamine alone. After ingestion and accumulation of microplastics, the enantioselectivity, BCFs, BMFs, and distribution of methamphetamine were significantly altered. These results provide evidence that the co-occurrence of microplastics and the chiral drug methamphetamine may increase the burden on aquatic species, with potential further impacts throughout aquatic food chain.